PRODUCT DEVELOPMENT AND PRODUCT INNOVATION OF TEH HIJAU CAP POHON KURMA (A Study on PT Panguji Luhur Utama) - Indrasari, Meithiana; Purnomo, Bambang Raditya; Yunus, Eddy (Journal of Technology Management and Business, 2017)
This research aims to explain and analyze product development strategy and product innovation of Cap Pohon Kurma Green Tea. Descriptive method with qualitative approach is a type of research used by researchers. The purpose of this research so that researchers can describe the actual situation in accordance with reality, digging and analyzing more deeply related to product development strategy and product innovation by using observation, interview and documentation in data collection techniques. The results of this study indicate that the process of product development should be done pro-active with still pay attention to financial performance of company (financial performance) so that what is expected by consumer in market can also fulfill expectation from shareholders (stockholders). Â Keywords: Product Development, Product Innovation, Green Tea, Descriptive Qualitative